Respuesta :

Answer:

[tex]f(3x)=9x^2-3[/tex]

Step-by-step explanation:

One is given the following function:

[tex]f(x)=x^2-3[/tex]

One is asked to evaluate the function for ([tex]f(3x)[/tex]). Substitute ([tex]3x[/tex]) in place of ([tex]x[/tex]) then simplify. Remember that a number raised to an exponent is the same as that number times itself the number of times that the exponent indicates. One can apply this logic here while simplifying,

[tex]f(x)=x^2-3[/tex]

[tex]f(3x)=(3x)^2-3[/tex]

[tex]f(3x)=(3x*3x)-3[/tex]

[tex]f(3x)=(9x^2)-3[/tex]

[tex]f(3x)=9x^2-3[/tex]